Basophils and Autoreactive IgE in the Pathogenesis of Systemic Lupus Erythematosus - Charles, Nicolas; Rivera, Juan (Current allergy and asthma reports, 2011)
Systemic lupus erythematosus (SLE) is a heterogeneous disease that can affect multiple organs. A hallmark of this disease, as is the case for other autoimmune diseases, is the presence of large numbers of autoantibodies. As such, SLE is considered to be a B-cell disease perpetuated by the expansion of autoreactive T and B cells. The T cells involved have long been considered to be T-helper type 1 (Th1) and Th17 cells, as these potent proinflammatory cells can be found in the tissues of SLE patients. Recent advances point to a role for the Th2 environment in contributing to SLE through promotion of autoantibody production. Here we describe the recent work focusing on autoreactive IgE and the activation of basophils as promoting the production of autoantibodies in SLE. The findings, both in a murine model of SLE and in humans with SLE, support the concept that the activation of the basophil by autoreactive IgE-containing immune complexes serves to amplify the production of autoantibodies and contributes to the pathogenesis of disease. We propose that therapeutic targeting of this amplification loop by reducing the levels of circulating autoreactive IgE may have benefit in SLE.